Safe and sustainable lithium-ion batteries - Kallitsis,E; Lander,L; Edge,J; Bravo,Diaz L; Brown,A; Kelsall,G; Offer,G; Korre,A (Imperial College London - Energy Futures Lab, 2022)
The transition to clean energy and electric mobility is driving unprecedented demand for lithium-ion batteries (LIBs). This paper investigates the safety and sustainability of LIBs, exploring ways of reducing their impact on the environment and ensuring they do not pose a danger to health of workers or users.